Performativitas dalam novel Mbojo Mambure karya Parange Anaranggana - Naila Fauziah; Wening Udasmoro (Aksara: Jurnal Bahasa dan Sastra, 2022)
The transvestite often become the main character in the literature. One of the writers who present the transvestite is Parange Anaranggana through Mbojo Mambure (later shorten as MM) novel. MM is a realist literature based on social reality in the Bima district. Bima’s people are still shackled inside binary gender, which is the label between men to masculinity and women to feminine. Meanwhile, non-binary gender gets several deficient labels from the local community. In the MM, the transvestite is often get verbal violence and shackled into social discourse. This situation makes them want to get out of the construction built by society. The purpose of this study is to explain several performativities of the transvestite entity amid heteronormative idealism society. This study uses Judith Butler’s performativity theory. Butler explains performativity is some of the discursive practice which generates or assign discourse production. The method in this study is qualitative, which explains there are transvestites who express gender through some performances or actions, appearance and conversation. The transvestite wants to show they could live together with society. Second, Parange Anaranggana described the transvestite who come back to initial identity. Two transvestites experience ambivalence inside themselves. Third, the description of transvestite who come back to initial identity confirms that they could not change stigma in society. Nevertheless, the transvestite could represent a new point of view that Bima has a variety of gender. Keywords: gender, the transvestite, performativities, Bima.